Caspase activity and oxidative stress of granulosa cells are associated with the viability and developmental potential of vitrified immature oocytes. (March 2016) - Wei, Jian-Hong; Yuan, Xin-Yan; Zhang, Jian-Min; Wei, Jian-Qiang
Abstract: Objective: The aim of this study is to determine whether caspase activity and oxidative stress of granulosa cells are associated with the viability and developmental potential of vitrified immature oocytes. Study design: Oocytes from mice were exposed to genistein or/and Z-VAD-FMK with or without vitrification. Ultrastructural alterations of granulosa cells in vitrified immature oocytes were observed. Moreover, the level of superoxide dismutase (SOD) in granulosa cells, incidence of apoptotic follicles, the viability of vitrified-warmed oocytes and their subsequent developmental competence were measured. Results: Ultrastructural alterations of granulosa cells vitrified in the presence of genistein or Z-VAD-FMK were slighter than that of granulosa cells vitrified in the absence of genistein or Z-VAD-FMK. The incidence of apoptotic follicles vitrified in the presence of genistein or Z-VAD-FMK was significantly lower than that of immature oocytes vitrified in the absence of genistein or Z-VAD-FMK, whereas, the level of SOD in granulosa cells, the viability and developmental competence of immature oocytes vitrified in the presence of genistein or Z-VAD-FMK were significantly higher than that of immature oocytes vitrified in the absence of genistein or Z-VAD-FMK. Conclusion: Both antioxidant (genistein) and caspase inhibition (Z-VAD-FMK) improve the viability and developmental competence of vitrified immature oocytes. Genistein is superior to Z-VAD-FMK in improving the efficacy of immature oocyte vitrification.